Comparison of Microalgae Harvesting Methods: Technical Efficiency and Economic Feasibility for Scalable Biofuel Production - Budiarto, Andy; Hardianto, Ari; Syihab, Abu Bakar Muhammad Ibnu; Sidquni, Saifa Aprilia; Adinisa, Lucy; Nurjannah, Ivani; Subroto, Toto (Trends in Sciences, 2026)
Global warming is a critical global challenge that has accelerated the development of carbon mitigation strategies. Microalgae-based systems have emerged as a promising carbon capture and utilization (CCU) approach, often referred to as BioCCU, due to their ability to convert captured captured carbon into valuable biomass. In the energy sector, algal biomass can be converted into diverse biofuels such as high-calorie biomass, biodiesel, bioethanol, and hydrogen. Despite this potential, large-scale deployment of microalgae-based CCU systems is still constrained by the harvesting stage, which remains one of the most energy- and cost-intensive processes. This review provides a comparative assessment of microalgae harvesting techniques such as centrifugation, filtration, and coagulation/flocculation, focusing on energy consumption, operational cost, biomass quality, and technical feasibility for BioCCU applications. The analysis is based on laboratory- and pilot-scale data obtained from BioCCU unit at Paiton Power Plant Units 5 & 6, Indonesia, complemented by relevant literature. The results shows that centrifugation produces high-quality, contamination-free biomass but requires extremely high energy input, resulting in a low net energy ratio (NER) of 1.20 and a high operational cost of approximately USD 0.51/kg of dry biomass. Filtration shows improved energy performance (NER = 5.22) and low operational cost (USD 0.16/kg of dry biomass), but its application is limited by membrane fouling, operational complexity, and high moisture content of the harvested biomass. In contrast, coagulation–flocculation demonstrates the most favorable energy performance, achieving a high NER value of 21.34 with a relatively low operational cost of USD 0.21/kg of dry biomass, while offering simpler operation and more energy-efficient downstream drying. The main contribution of this review lies in quantifying the trade-offs among harvesting methods and identifying coagulation–flocculation as the most promising option for large-scale BioCCU systems targeting biofuel production, provided that future developments address the environmental impacts of chemical usage. HIGHLIGHTS This review evaluates three major microalgae harvesting techniques, such as centrifugation, filtration, and coagulation/flocculation for biofuel-oriented BioCCU applications. Compares methods based on technical efficiency, energy demand, and cost-effectiveness within sustainable energy frameworks. Identifies trade-offs between recovery efficiency and operational scalability for each harvesting approach. Provides insights for optimizing microalgae harvesting strategies to enhance BioCCU process integration and biofuel production sustainability. GRAPHICAL ABSTRACT